MAKE-UP AND ALTERATION - Helsloot, Niels (Daimon Revista Internacional de Filosofia, 1990)
Wittgenstein denies that language games can be determined by fixed rules. In section 83 of his Philosophical Investigations, he asks us to imagine the case where we play and make up/alter the rules as we go along. The relationship between make-up and alteration thus introduced has been interpreted in quite different ways. Kripke raises the sceptical ’paradox’ that one cannot know how to follow a rule- a private problem he solves scptically by appealing to community agreement. But also the community does not offer a fixed ground of regularity. Baker and Hacker therefore consider Kripke´s problem unsolvable. Wittgenstein would escape its consequences by not posing such meaningless question in the first place. In practice, a sceptical problem does not rise, for we use to know what to do- even without last grounds. This refusal to go into unsolvable problems, however, presupposes an undisputed ’we’. Through an orientation towards Derrida, Staten abandons such presupposed grounds more thoroughly. Feeling under the spell of a rule does not exclude deviant ways of going along. New ’appearances’ can always be identified to earlier instances or be distinguished from them as we go along. Making such difference is part of the game of rule following.